Experience of combined treatment of the chronic apical periodontitis implementing surgical procedures (Эндодонтия Today, 2020)
The goal of the present study was to evaluate the efficacy of the combined therapeutical and surgical treatment of chronic apical periodontitis in lower first molars. The Department of Dental Propedeutics has accumulated a big experience of this kind of procedures. Results of the study have shown in case of periapical lesion presence after a period of treatment with temporary fillings combination of conservative and surgical treatment significantly increases the positive prognosis for the treated tooth.